1, 2, 5, 6‐Tetrakis(guanidino)‐Naphthalenes: Electron Donors, Fluorescent Probes and Redox‐Active Ligands. Issue 26 (21st April 2020) - Lohmeyer, Lukas; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans‐Jörg
Abstract: New redox‐active 1, 2, 5, 6‐tetrakis(guanidino)‐naphthalene compounds, isolable and storable in the neutral and deep‐green dicationic redox states and oxidisable further in two one‐electron steps to the tetracations, are reported. Protonation switches on blue fluorescence, with the fluorescence intensity (quantum yield) increasing with the degree of protonation. Reactions with N ‐halogenosuccinimides or N ‐halogenophthalimides led to a series of new redox‐active halogeno‐ and succinimido‐/phthalimido‐substituted derivatives. These highly selective reactions are proposed to proceed via the tri‐ or tetracationic state as the intermediate. The derivatives are oxidised reversibly at slightly higher potentials than that of the unsubstituted compounds to dications and further to tri‐ and tetracations. The integration of redox‐active ligands in the transition‐metal complexes shifts the redox potentials to higher values and also allows reversible oxidation in two potentially separated one‐electron steps. Abstract : Redox‐active guanidines : New redox‐active guanidines, stable in the neutral as well as dicationic redox states and reversibly oxidisable up to the tetracations, were synthesised. Protonation switches on fluorescence; reactions with N ‐halogenosuccinimides (NXS) and ‐phthalimides selectively gives fully substituted derivatives. Coordination of palladium acetate yields binuclear complexes in which the bridging guanidine ligands are oxidisable in two reversible one‐electron steps.